LITERATURE REVIEW ON BUDGET IN FIVE YEARS IN INTERNATIONAL JOURNALS FROM 2000 TO 2009 REVISIÓN DE LA LITERATURA SOBRE EL PRESUPUESTO EN CINCO PERIÓDICOS INTERNACIONALES DESDE EL AÑO 2000 HASTA EL 2009 REVISÃO DA LITERATURA SOBRE ORÇAMENTO EM CINCO PERIÓDICOS INTERNACIONAIS NOS ANOS DE 2000 ATÉ 2009 - Giancarlo Gomes; Carlos Eduardo Facin Lavarda; Edson Wilson Torrens (REGE Revista de Gestão, 2013)
This article analyzed the scientific production budget in the literature. The budget is a combination of information flow, administrative processes and procedures which are part of the short-term planning and control system of an organization. Regarding the research plan, this work is characterized as descriptive, longitudinal, and as a means of documentary research. The research is of type desk research and sought publications in a period between 2000 and 2009. It was found that over a period of 10 years, there were 40 international and 11 national papers dealing with budget. Stands a concentration  of publications in the journal Organization & Accounting Society. The year 2000 had the highest number of publications. Most of the articles were undertaken by one or two authors. The survey was the predominant type of research. The work that has figured more times the references of these articles was "Participative Budgeting: The Effects of Risk Aversion and Asymmetric Information on Budgetary Slack" the researcher Mark S. Young (1995). Although referenced less often, the books still figured as the second largest source of research, highlighting the most of them referenced Multiple Regression in Behavioral Research author Elazar Pedhazur (1982) with five references. The issue in Brazil is incipient in relation to the amount of work done abroad. El presente artículo analizó la producción científica en el área de presupuesto en la literatura internacional. El presupuesto es una combinación de flujo de información, procesos y procedimientos administrativos, los cuales son parte integrante del planeamiento de corto plazo y del sistema de control de una organización. En relación al plano de investigación, este trabajo se caracteriza como descriptivo, longitudinal y teniendo como forma la investigación documental. La investigación es del tipo desk research, abarcando un período de publicaciones entre 2000 y 2009. Se verificó que en un período de 10 años fueron publicados 40 trabajos internacionales y 11 nacionales sobre presupuesto. Se destaca una concentración de publicaciones en el periódico  Accounting Organization & Society. El año de 2000 presentó la mayor cantidad de publicaciones. La mayor parte de los artículos fue desarrollada por uno o dos autores. La investigación predominante fue del tipo levantamiento. La obra que figuró más veces en el referencial de esos artículos fue Participative Budgeting: The Effects of Risk Aversion and Asymmetric Information on Budgetary Slack, del investigador Mark S. Young (1985). A pesar de aparecer en las referencias menos veces, los libros todavía figuraron como la segunda mayor fuente de investigación, destacándose como el más mencionado de ellos, Multiple Regression in Behavioral Research, del autor Elazar Pedhazur (1982), con cinco referencias. El tema, en Brasil, es incipiente, en comparación a la cantidad de trabajos desarrollados en el exterior O presente artigo analisou a produção científica na área de orçamento na literatura internacional. O orçamento é uma combinação de fluxo de informação, processos e procedimentos administrativos, os quais são parte integrante do planejamento de curto prazo e do sistema de controle de uma organização. Em relação ao plano de pesquisa, este trabalho se caracteriza como descritivo, longitudinal e tendo como forma a pesquisa documental. A pesquisa é do tipo desk research, compreendendo um período de publicações entre 2000 e 2009. Verificou-se que, em um período de 10 anos, foram publicados 40 trabalhos internacionais e 11 nacionais sobre orçamento. Destaca-se  uma concentração de publicações no periódico  Accounting Organization & Society. O ano de 2000 apresentou a maior quantidade de publicações. A maior parte dos artigos foi desenvolvida por um ou dois autores. A pesquisa predominante foi do tipo levantamento. A obra que figurou mais vezes no referencial desses artigos foi  Participative Budgeting: The Effects of Risk Aversion and Asymmetric Information on Budgetary Slack, do pesquisador Mark S. Young (1985). Apesar de referenciados menos vezes, os livros ainda figuraram como a segunda maior fonte de pesquisa, destacandose o Multiple Regression in Behavioral Research, do autor Elazar Pedhazur (1982), com cinco referências. O tema, no Brasil, é incipiente, comparativamente à quantidade de trabalhos desenvolvidos no exterior.